Smallholders need to be involved in the decision-making - Unwin, Tim (Technical Centre for Agricultural and Rural Cooperation, 2019)
Tim Unwin discusses what is needed in ICT for Development collaboration and initiatives to ensure technology and data can truly benefit smallholder farmers.